1980
DOI: 10.1029/ja085ia13p08026
|View full text |Cite
|
Sign up to set email alerts
|

Zonal and meridional circulation of the lower atmosphere of Venus determined by radio interferometry

Abstract: From earth‐based Doppler and interferometric radio observations we determined the paths, in three dimensions and as functions of time, taken by the Pioneer probes as they fell to the surface of Venus. From the motion of each probe below about 65‐km altitude we were able to infer the ambient wind velocity with an estimated uncertainty of about 1 m s−1 in each vector component. The magnitude of the velocity was about 1 m s−1 or less near the surface of the planet and about 100 m s−1 near 65‐km altitude at all fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(61 citation statements)
references
References 15 publications
(6 reference statements)
1
60
0
Order By: Relevance
“…For entry probe data such as Pioneer Large and Small probes, the hydrostatic law is required for pressure and altitude calculations (Seiff et al 1980). Interestingly, although the Pioneer probes were tracked using DLBI (Counselman et al 1980), there appear to be no estimates of the distance of the falling probes relative to the planet, which should have been possible from the DLBI data. A comparison of the tracking derived altitudes with the Seiff et al (1980) values would have revealed a discrepancy due to the constant molecular weight assumption.…”
Section: Vertical Gradient Of Atmospheric Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…For entry probe data such as Pioneer Large and Small probes, the hydrostatic law is required for pressure and altitude calculations (Seiff et al 1980). Interestingly, although the Pioneer probes were tracked using DLBI (Counselman et al 1980), there appear to be no estimates of the distance of the falling probes relative to the planet, which should have been possible from the DLBI data. A comparison of the tracking derived altitudes with the Seiff et al (1980) values would have revealed a discrepancy due to the constant molecular weight assumption.…”
Section: Vertical Gradient Of Atmospheric Compositionmentioning
confidence: 99%
“…Longitudinal differences from surface to the cloud tops (∼ 70 km) are < 5 K in low latitudes (Seiff et al 1980;Kliore 1985) and can be ∼ 20 K in higher latitudes (> 60°). In the deep atmosphere, at 10 km altitude, winds are as fast as 5 m s −1 (Counselman et al 1980), suggesting at least some meridional temperature gradient must exist if the flow is cyclostrophic. Given the large thermal inertia, the temperature differences in the near surface atmosphere are expected to be small in the deep atmosphere (Stone 1975).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of such strong superrotation is a mystery of the general circulation of planetary atmospheres. The observed equatorial westward wind of the Venus atmosphere achieves a speed of -100 m s −1 at the cloud-top level of -65 km altitude (e.g., Counselman III et al 1980). This zonal wind is about 55 times faster than the planetary rotation speed at the equator.…”
Section: Introductionmentioning
confidence: 84%
“…or albedo of the clouds, or it may represent real changes While this is not strictly true, cloud-tracked wind velocities in the flow field at a fixed elevation. We make the assumpdo agree with in situ and spectroscopic measurements (for tion that average streak orientations within a single epoch example, spectroscopy: Traub and Carleton 1975; Pioneer can be used to infer a meaningful estimate of the average Venus probes: Counselman et al 1980; VEGA balloons: flow field. Sagdeev et al 1986).…”
Section: Introductionmentioning
confidence: 96%